Strategi Dinas Perhubungan dalam Penertiban Parkir di Kota Wisata Bukittinggi - Fadel Afifi, Rizki; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to identify the strategies implemented by the Bukittinggi City Transportation Agency in curbing parking in the city's tourist areas. This research used a qualitative and descriptive approach and was conducted at the Bukittinggi City Transportation Agency. Research informants were selected using a purposive sampling technique. Data were collected through observation, interviews, and documentation and analyzed using SWOT. The results showed that the strategies carried out by the Transportation Agency include providing parking facilities and infrastructure, strengthening human resources, and socializing with the community. However, several inhibiting factors cause this strategy not to be implemented optimally, including the lack of public awareness to comply with parking regulations, officer indiscipline, and the limited authority of the transportation agency in taking action against parking violations. This research concludes that although the Bukittinggi City Transportation Office has tried to overcome the existing obstacles, the strategies implemented still need to be improved to achieve maximum results.